Dentoxanthus iranicus Stephensen, 1946 (Crustacea: Brachyura: Galenidae): a new record from Gujarat, India, with systematic notes. (2nd September 2015) - Ng, Peter K.L.; Trivedi, Jignesh N.; Vachhrajani, Kauresh D.
Abstract : The rare pilumnoid crab, Dentoxanthus iranicus Stephensen, 1946 (Galenidae), is recorded from Gujarat state in India for the first time. Originally described from a small female (Gulf of Oman), and subsequently reported twice from Pakistan on the basis of two males and a female, the species is not well known and has never been described to modern standards. On the basis of the present male specimen from India, as well as a previously unreported male specimen from Pakistan, the species is redescribed and its systematics discussed.